Epidemiology, phylogeny and genetic characterization of carbapenem-resistant Citrobacter spp. from 5 hospitals in China - Qiang Zhao; Ling Guo; Kun Ye; Lifeng Wang; Jiyong Yang; Liyan Ye (Journal of Global Antimicrobial Resistance)
ABSTRACT: Objectives: Carbapenem-resistant Citrobacter spp. (CRC) are increasingly recognized as healthcare-associated pathogens, while systematic studies on clinical epidemiology, genetic diversity, and resistant mechanisms of CRC are relatively scarce. The present study provides comprehensive and systematic research on CRC. Methods: Clinical isolates of Citrobacter spp. resistant to carbapenems were collected from 5 hospitals across China between October 2014 and December 2017. All the isolates were identified by MALDI-TOF MS and FastANI. Whole-genome sequencing and phylogenetic analyses were performed. Sequencing data were analyzed using MLST, PlasmidFinder, ResFinder, and ISFinder tools. Results: Thirty-one CRC isolates were isolated from 5 hospitals in different provinces. These strains exhibited significant phylogenetic divergence. ST85 (12.90%) and ST116 (12.90%) were the predominant STs. NDM (41.94%), KPC-2 (25.81%), and IMP (19.35%) were the most frequent carbapenemases of CRC. Interestingly, KPC is frequently associated with C. freundii, while NDM is predominantly observed in C. portucalensis. All the IncX3 and IncN-type plasmids carrying blaNDM and most non-typeplasmids carrying blaKPC were transferrable by conjugation. The genes blaNDM and blaKPC were primarily located within relatively conserved genomic environments, including “ISAba125-blaNDM-bleMBL-trpF-dsbD-cutA1-groES-groEL-ISCR27” and “Tn3 transposase-ISKpn27-blaKPC-2-△ISKpn6-korC-kclA-hp-hp-△repB-TnAS1”. Conclusions: The clonal transmission of CRC and the conjugative antibiotic resistance plasmids were the key mechanisms driving the spread of multidrug resistance. It highlights the need to strengthen molecular surveillance, with a focus on high-prevalence clones such as ST85 and ST116 carrying mobile resistance elements.